Parental, pregnancy and neonatal characteristics during the perinatal period as potential risk factors for childhood cancer: FeToxCancer case-control study - Anja Stajnko; Jesse Daniel Thacher; Anna Oudin; Christian Lindh; Thomas Lundh; Ingrid Øra; Jenny Selander; Lars Rylander; Maria Albin; Karin Källén; Karin Broberg (PLoS ONE, 2026)
Childhood cancer aetiology is poorly understood and is considered to originate in utero and early postnatal life. In this study, we investigated perinatal characteristics as potential risk factors by performing a population-based case-control study, including 1340 cancer cases diagnosed < 19y and born between 1989–2021 in southern Sweden, and 13400 controls matched by sex, year, and municipality of birth. Perinatal characteristics were obtained from seven national registries. Cox regression was used to examine the associations between perinatal characteristics and the risk of overall childhood cancer, leukaemia, CNS tumours, lymphoma, and other cancer types combined (OCT). Large for gestational age was associated with a higher risk of overall cancer (HR, 95%CI: 1.32, 1.02–1.69) and leukaemia (HR, 95%CI: 1.58, 1.01–2.5), while a 5-min Apgar score <7 indicated a higher risk of OCT (HR, 95%CI: 2.16, 1.12–4.15). Mechanical ventilation during neonatal care was associated with a higher risk of overall cancer (HR, 95%CI: 1.88, 1.39–2.53) and OCT (HR, 95%CI: 2.09, 1.19–3.39). The aforementioned characteristics were associated with up to a threefold increased risk among children diagnosed before six months of age compared to those diagnosed later. Additionally, maternal obesity was associated with a higher risk of CNS tumours (HR, 95%CI: 1.51, 1.04–2.21) and lymphoma (HR, 95%CI: 2.26, 1.31–3.88), and maternal underweight with a higher risk of leukaemia (HR, 95%CI: 2.43, 1.40–4.22). Planned caesarean delivery indicated an increased risk of OCT (HR, 95%CI: 1.52, 1.04–2.22). Our findings identify several perinatal characteristics associated with childhood cancer risk, highlighting the perinatal period as an important window for future etiological research.